Analisis pemanfaatan buah mangrove Rhizophora mucronata dalam mendukung wisata mangrove masyarakat Kampung Mandar Kabupaten Banyuwangi - Fattah, Mochammad; Hakim, Luchman; Soemarno, Soemarno; Purwanti, Pudji (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
The use of mangrove fruit to create economic benefit for the community is anticipated to bolster conservation efforts for the mangrove environment. In Mandar Banyuwangi Village, one application of mangrove fruit is its conversion into flour. This study aimed to examine the proximate composition of Rhizophora mucronata mangrove flour and evaluate the profitability of processing this flour into pastries. The analysis conducted encompasses the proximate content test (including protein, fat, water, ash, and carbs) and a profit analysis that factors in the cost of goods sold (COGS). Mangrove flour manufactured by Poklahsar “Mina UPA Karya” is derived from the fruit of Rhizophora mucronata. The processing method necessitated seven days to manufacture mangrove flour. The proximate composition of mangrove flour, as per SNI criteria, includes water and carbohydrate content, although protein, fat, and ash content are marginally over or below SNI specifications. Mangrove flour is utilized in a variety of desserts, including nastar, kastengel, cookies, almond chocolate, roses, jam sumprit, chocolate sumprit, peanut cake, and krispi brownies. Products made using processed mangrove flour in pastries yield a profit margin of 9.16% of the cost of goods sold (COGS). The R/C, BEPs, BEPq, profit, and profitability ratio of the mangrove flour processing business indicate profitability, since they go over the minimum requirements of profitability criteria.